Respuesta :
For this case we have the following functions transformation:
Vertical expansions:
To graph y = a * f (x)
If a> 1, the graph of y = f (x) is expanded vertically by a factor a.
f1 (x) = (3x) ^ 2
Horizontal translations
Suppose that h> 0
To graph y = f (x-h), move the graph of h units to the right.
f2 (x) = (3x-6) ^ 2
Vertical translations
Suppose that k> 0
To graph y = f (x) + k, move the graph of k units up.
g (x) = (3x-6) ^ 2 + 3
Answer:
expanded horizontally by a factor of 3, horizontal shift rith 6, vertical shift up 3
Vertical expansions:
To graph y = a * f (x)
If a> 1, the graph of y = f (x) is expanded vertically by a factor a.
f1 (x) = (3x) ^ 2
Horizontal translations
Suppose that h> 0
To graph y = f (x-h), move the graph of h units to the right.
f2 (x) = (3x-6) ^ 2
Vertical translations
Suppose that k> 0
To graph y = f (x) + k, move the graph of k units up.
g (x) = (3x-6) ^ 2 + 3
Answer:
expanded horizontally by a factor of 3, horizontal shift rith 6, vertical shift up 3
Answer:
C. Compressed horizontally by a factor of 1/3, horizontal shift right 2, vertical shift up 3
Step-by-step explanation:
If a function f(x) is transformed and make f(kx),
f(x) is compressed horizontally by the factor 1/k if k > 1
f(x) is stretched horizontally by the factor 1/k if 0 < k < 1
Also, if f(x) is transformed and make f(x+a),
f(x) is shifted right if a < 0
f(x) is shifted left if a > 0,
Now, if f(x) gives f(x) + k after transformation,
f(x) is shifted vertically k unit up if k > 0,
f(x) is shifted vertically k unit down if k < 0,
Here, the parent function,
[tex]f(x) = x^2[/tex]
transformed function,
[tex]g(x)=(3x-6)^2+3=(3(x-2))^2+3[/tex]
Thus, by the above explanation,
f(x) is compressed horizontally by a factor of 1/3, horizontal shift right 2, vertical shift up 3.
Option C is correct.